Carcinogenic activity of PbS quantum dots screened using exosomal biomarkers secreted from HEK293 cells - Kim JH (Dove Medical Press, 2015)
Jung-Hee Kim,1 Hye-Rim Kim,2 Bo-Ram Lee,1 Eun-Sook Choi,1 Su-Il In,2 Eunjoo Kim11Division of Nano and Energy Convergence Research, 2Department of Energy Systems Engineering, DGIST, Daegu, Republic of KoreaAbstract: Lead sulfide (PbS) quantum dots (QDs) have been applied in the biomedical area because they offer an excellent platform for theragnostic applications. In order to comprehensively evaluate the biocompatibility of PbS QDs in human cells, we analyzed the exosomes secreted from cells because exosomes are released during cellular stress to convey signals to other cells and serve as a reservoir of enriched biomarkers. PbS QDs were synthesized and coated with 3-mercaptopropionic acid (MPA) to allow the particles to disperse in water. Exosomes were isolated from HEK293 cells treated with PbS–MPA at concentrations of 0 µg/mL, 5 µg/mL, and 50 µg/mL, and the exosomal expression levels of miRNAs and proteins were analyzed. As a result, five miRNAs and two proteins were proposed as specific exosomal biomarkers for the exposure of HEK293 cells to PbS–MPA. Based on the pathway analysis, the molecular signature of the exosomes suggested that PbS–MPA QDs had carcinogenic activity. The comet assay and expression of molecular markers, such as p53, interleukin (IL)-8, and C-X-C motif chemokine 5, indicated that DNA damage occurred in HEK293 cells following PbS–MPA exposure, which supported the carcinogenic activity of the particles. In addition, there was obvious intensification of miRNA expression signals in the exosomes compared with that of the parent cells, which suggested that exosomal biomarkers could be detected more sensitively than those of whole cellular extracts.Keywords: comet assay, DNA damage, exosome, high-throughput screening, lead sulfide quantum dots (PbS QDs), nanoparticle toxicity